Primary Small Cell Carcinoma of the Hypopharynx: A Report of Two Cases and Review of Nine Additional Cases - Mitsuhiko Nakahira; Kiyomi Kuba; Satoko Matsumura; Masashi Sugasawa (Case Reports in Otolaryngology)
Objective. Two patients with primary small cell carcinoma (SmCC) of the hypopharynx, an extremely rare site for the occurrence of SmCC, are reported and nine additional well-documented cases are reviewed. Methods. Case report and review of the literature concerning primary SmCC of the hypopharynx. Results. On the final analysis, we reviewed eleven cases of primary SmCC of the hypopharynx. The tumors contained mixed elements of SmCC and squamous cell carcinoma (SCC) in six (55%) of eleven patients. Out of eleven patients, two patients had distant metastasis at the initial presentation. Even though nine patients presented with locoregional disease, development of distant metastasis after treatment was seen in five patients (56%), whereas there was no report of treatment failure on the primary site. To achieve more than two-year survival, patients should have received more than 4 cycles of chemotherapy. Conclusion. We report two cases of primary SmCC of the hypopharynx with a review of the literature. In more than half of the cases, combined carcinomas with SCC are seen. Because this tumor has a strong propensity for distant metastasis even in patients with clinically localized tumor, new powerful systemic agents should be explored.